2016
DOI: 10.1007/s10661-016-5317-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring of the area surrounding oil wells in Val d’Agri (Italy): element accumulation in bovine and ovine organs

Abstract: In this work, environmental heavy metal contamination in the Val d'Agri area of Southern Italy was monitored, measuring the accumulation of 18 heavy metals (U, Hg, Pb, Cd, As, Sr, Sn, V, Ni, Cr, Mo, Co, Cu, Zn, Ca, Mn, Fe, and Al) in the organs of animals raised in the surrounding area (kidney, lung, and liver of bovine and ovine species). Val d'Agri features various oil processing centers which are potentially a significant source of environmental pollution, making it essential to perform studies that will ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Table 2 shows that the value of aluminum in cow sample of both control group and study area is 186.2 and 278.7 ppb, respectively, again the value of study area is higher than the control group by 1.4 times. Both locations have a similar value for aluminum, but in comparison with the WHO 2017 guidelines which are 200 ppb, both locations are higher than allowed limit that is due to the type of animal diet in both the groups [17].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Table 2 shows that the value of aluminum in cow sample of both control group and study area is 186.2 and 278.7 ppb, respectively, again the value of study area is higher than the control group by 1.4 times. Both locations have a similar value for aluminum, but in comparison with the WHO 2017 guidelines which are 200 ppb, both locations are higher than allowed limit that is due to the type of animal diet in both the groups [17].…”
Section: Resultsmentioning
confidence: 77%
“…Both Al and Fe are effective exceeding the WHO guideline, as discussed in the first section high value of Al is due to the type of both animals' diet in the study area [17]. Fe is higher than the WHO standards in both animal meat samples, but it is very high in cows' meat samples as showed above.…”
Section: Section Two: Comparing Study Area With the Who 2017 Standardsmentioning
confidence: 64%
“…Environmental pollution is a topic of great interest because it directly affects the quality of ecosystems and of all living organisms at different trophic and systematic levels (Ferrante et al, 2017). In recent years, water pollution by heavy metals such as lead (Pb) and cadmium (Cd) has accelerated dramatically due to natural and anthropogenic source (Masindi and Muedi, 2018) and subsequently, these metals are taken by plants and animals and take their way into food chain (Miedico et al, 2016). In Matrouh governorate, the native rangelands are deteriorating due to environmental and human reasons (Halmy, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies assessed heavy metals in organs of animals raised in oil producing regions and slaughtered for meat consumption. Researchers found that among sheep (but not cattle), proximity to oil wells was related to higher concentrations of Pb (liver) and Cd (kidney) and that levels of metals varied by geographic location of the livestock in southern Italy (Miedico et al 2016). Among cattle in oil-producing regions in Colombia, Pb, Cd, and molybdenum were measured in the organs of slaughtered animals (Brown 2003).…”
Section: Animal Biomonitoringmentioning
confidence: 99%